Overcoming Challenges to Make Bacteriophage Therapy Standard Clinical Treatment Practice for Cystic Fibrosis - Ng, Renee N.; Tai, Anna S.; Chang, Barbara J.; Stick, Stephen M.; Kicic, Anthony (Frontiers in Microbiology, 2021)
Individuals with cystic fibrosis (CF) are given antimicrobials as prophylaxis against bacterial lung infection, which contributes to the growing emergence of multidrug resistant (MDR) pathogens isolated. Pathogens such as Pseudomonas aeruginosa that are commonly isolated from individuals with CF are armed with an arsenal of protective and virulence mechanisms, complicating eradication and treatment strategies. While translation of phage therapy into standard care for cystic fibrosis has been explored, challenges such as the lack of an appropriate animal model demonstrating safety in vivo exist. In this review, we have discussed and provided some insights in the use of primary airway epithelial cells to represent the mucoenvironment of the CF lungs to demonstrate safety and efficacy of phage therapy. The combination of phage therapy and antimicrobials is gaining attention and has the potential to delay the onset of MDR infections. It is evident that efforts to translate phage therapy into standard clinical practice have gained traction in the past five years. Ultimately, collaboration, transparency in data publications and standardized policies are needed for clinical translation.